Kualitas Pupuk Organik Cair Dari Urine Sapi Pada Beberapa Waktu Simpan - Lena Walunguru (Partner, 2012)
Quality of Liquid Organic Fertilizer from Cattle Urine on Different Time Store. The research aimed to investigate save time of liquid organic fertilizer from cattle urine to value of N, P, and K available. The research used Randomized Completed Block Design (RCBD) with six treatments and three replications. The treatments were liquid organic fertilizer from cattle urine stored for 0 week (T0); liquid organic fertilizer from cattle urine stored for 2 weeks (T1); organic fertilizer  from cattle urine stored for 4 weeks (T2); organic fertilizer  from cattle urine stored for 6 weeks (T3); organic fertilizer  from cattle urine stored for 8 weeks (T4); and organic fertilizer  from cattle urine stored for 10 weeks (T5). Statistical analysis used was the Analysis of Variance and Honestly Significant (HSD) at 5% significant level. The result of research treatment of liquid organic fertilizer from cattle urine stored for 0 weeks (To) contains an average of available N as 5:27, the content was reduced to 3.4% at 10 weeks old store.  Available N reduced by 1.87% is equivalent to 35.48%, shows considerable loss of  available N. The average levels of available P in a liquid organic fertilizer from cattle urine that has been stored for 0 weeks (To) is 64 ppm. The average levels of available P in a liquid organic fertilizer from cattle urine that has been stored for 10 weeks is 60 ppm, has been reduced as much as 4 ppm equivalent to 6.25% compared to T0. The average levels of available K are liquid organic fertilizer from cattle urine that has been stored from 0 to 10 weeks tended to decrease in the least amount. Liquid organic fertilizer from cattle urine which has been stored for 0 weeks (To) having an average grade of  available K at 16.82 ppm, the content to be 16.57 ppm at 10 weeks old (T5). Available K has been reduced as much as 0.25 ppm equivalent to 1.49% which showed no significant decline.Key words: liquid organic fertilizer from cattle urine, store time, N available, P available, and K available